DETERMINATION OF SOME HEAVY METALS IN SOLID WASTE FROM HAEVY WATER TREATMENT STATION IN BAGHDAD - & et al., Sultan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Solid waste of heavy water treatment stations is used in agriculture as a fertilizer. This practice may transfer polluted chemicals to human food chain. In this research study, nine heavy metals ( Pb, Co, Zn, Cu, Ni, Cr, Cd, As and Sb ) were studied in solid waste from main waste water treatment station in Baghdad/Alrusafa city by using Atomic Absorption Spectrometry (AAS) technique. Eight samples were chosen carefully during the period of  October 2016 to June 2017. The presented data showed that five of the studied metals have higher concentration as compared to others. The highly concentrated metals were [Pb (282.95), Zn (274.73), Cu (170.67), Ni (91.41), Co (29.45)], the concentration was measured in mg/kg. While [Cd (3.67), As (0.93), Sb (0.81), Cr (0.80) ] showed lower concentration. The results showed that the total concentration of studied heavy metals was ranged between 1220.35 mg/kg in February to  a low value of 562.63 mg/kg in October